Roadmap to Sustainable Textiles and Clothing Environmental and Social Aspects of Textiles and Clothing Supply Chain - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology,, 2014)
This book covers the elements involved in achieving sustainability in textiles and Clothing sector. The chapters to be covered in three volumes of this series title cover all the distinctive areas earmarked for achieving sustainable development in textiles and the clothing industry. This second volume deals with the measurement of environmental and societal impacts across the textiles and clothing supply chain. It addresses this important aspect in a comprehensive way including the overall picture of environmental and societal impacts of textiles and clothing supply chain, environmentally sustainable clothing consumption, emerging green technologies and eco-friendly products for sustainable textiles, etc. This volume has a dedicated place to deal with the consumer phase impacts in the life cycle of clothing products, biodegradation of textile products, sustainable business development and its implications in textile sector.